Complementary effects of pine bark extract supplementation on inattention, impulsivity, and antioxidative status in children with attention‐deficit hyperactivity disorder: A double‐blinded randomized placebo‐controlled cross‐over study. (8th February 2021) - Hsu, Cheng‐Dien; Hsieh, Li‐Hsuan; Chen, Ya‐Ling; Lin, I‐Cheng; Chen, Ying‐Ru; Chen, Chih‐Chi; Shirakawa, Hitoshi; Yang, Suh‐Ching
Abstract : The purpose of this study was to investigate the complementary effects of polyphenolic compounds from pine bark extract (PE) as a strong antioxidative substrate on the symptoms of inattention and impulsivity in children with attention‐deficit hyperactivity disorder (ADHD). This was a randomized, double‐blind, crossover, placebo‐controlled study that included two experimental units (4 weeks with PE supplementation and 4 weeks with placebo supplementation) separated by a 2‐week washout period. ADHD participants were supplemented with 25 mg or 50 mg PE. We recruited 20 participants (17 boys and 3 girls) with a mean age of 10.0 ± 2.1 years. PE supplementation caused a significant reduction in the inattention and hyperactivity‐impulsivity items of SNAP‐IV. During the period of PE supplementation, the item of commissions in the Continuous Performance Test III (CPT III) significantly decreased, which was used to evaluate the symptoms of inattention and impulsivity. In addition, the erythrocytic reduced glutathione/oxidized glutathione ratio significantly increased, and the plasma TBARs level significantly decreased after 4 weeks of PE supplementation. However, there was no significant correlation between CPT III (commission) and antioxidative status indictors. PE supplementation may have potential effects of ameliorating inattention and impulsivity, and elevating the antioxidative status in children with ADHD.